Youth songs: a type of Igbo choral music in Igbo Christian worship - Agu, Daniel C. C. (International Library of African Music, 1992)
This paper is concerned with the birth of the Youth Fellowship, acceptability, and the place of youth songs in Igbo Christian worship; with particular reference to the Niger Diocese of the Anglican Church of Nigeria, whose headquarters are at Onitsha, which is on the left bank of the river Niger in the South Eastern part of Nigeria.
Keywords: African Music